Applications of Information Theory to Economics and Finance - Singh, Ranjodh (Curtin University, 2019)
This thesis demonstrates the valuable contributions of information theory in analysing a diverse set of problems in Economics and Finance. Problems include predicting liquidation risk of financial assets, analysing cyclical behaviour of financial returns, searching for socio-economic determinants of body mass index and modelling population dynamics in regional and remote Australia. The results enhance our understanding of uncertainty associated with these problems and expand our existing techniques to analyse a wide range of socio-economic issues.